National-Level Safety Evaluation of Diverging Diamond Interchanges. Issue 7 (July 2019) - Nye, Timothy S.; Cunningham, Christopher M.; Byrom, Elizabeth
A national-level safety evaluation of Diverging Diamond Interchanges (DDIs) in the United States was completed. This study aimed to update previous evaluations and to expand the treatment group size of previous studies to provide a more robust and reliable safety assessment of DDI deployments. For this particular treatment, it was determined that, of the observational before-and-after evaluation methodologies, the comparison group approach yields the best evaluation results. The naïve method can be influenced by outside factors that cannot be accounted for (weather, crash reporting tendencies, etc.). The empirical Bayes method is unnecessary as DDIs are installed for operational benefits, meaning that risk of selection bias and regression-to-the-mean is minimal. This study recommends a total crashes crash modification factor (CMF) of 0.633 based on the comparison group analysis of 26 DDIs in 11 states. The comparison group method was also applied to a variety of crash variables for this study. Angle, rear-end, and sideswipe crashes were found to have CMFs of 0.441, 0.549, and 1.139, respectively. Fatal-and-injury crashes provided a CMF of 0.461. Daytime and nighttime crashes provided CMFs of 0.648 and 0.638, respectively.